A spoonful of L-fucose: an efficient therapy for GFUS-CDG, a new glycosylation disorder - Feichtinger, René; Hüllen, Andreas; Koller, Andreas; Kotzot, Dieter; Grote, Valerian; Rapp, Erdmann; Hofbauer, Peter; Brugger, Karin; Thiel, Christian; Mayr, Johannes A.; Wortmann, Saskia B. (EMBO molecular medicine, 2021)
Congenital disorders of glycosylation are a genetically and phenotypically heterogeneous family of diseases affecting the co- and posttranslational modification of proteins. Using exome sequencing, we detected biallelic variants in GFUS (NM_003313.4) c.[632G>A];[659C>T] (p.[Gly211Glu];[Ser220Leu]) in a patient presenting with global developmental delay, mild coarse facial features and faltering growth. GFUS encodes GDP-L-fucose synthase, the terminal enzyme in de novo synthesis of GDP-L-fucose, required for fucosylation of N- and O-glycans. We found reduced GFUS protein and decreased GDP-L-fucose levels leading to a general hypofucosylation determined in patient's glycoproteins in serum, leukocytes, thrombocytes and fibroblasts. Complementation of patient fibroblasts with wild-type GFUS cDNA restored fucosylation. Making use of the GDP-L-fucose salvage pathway, oral fucose supplementation normalized fucosylation of proteins within 4 weeks as measured in serum and leukocytes. During the follow-up of 19 months, a moderate improvement of growth was seen, as well as a clear improvement of cognitive skills as measured by the Kaufmann ABC and the Nijmegen Pediatric CDG Rating Scale. In conclusion, GFUS-CDG is a new glycosylation disorder for which oral L-fucose supplementation is promising.
Gesehen am 07.10.2021